Traveling interface modulations in the NH₃ + O₂ reaction on a Rh(110) surface - Rafti, Matías (2012)
A new type of traveling interface modulation has been observed in the NH₃ + O₂ reaction on a Rh(110) surface. A model is set up which reproduces the effect, which is attributed to diffusional mixing of two spatially separated adsorbates causing an excitability which is strictly localized to the vicinity of the interface of the adsorbate domains.